Method for preparing nanoscale carbon black from waste rubber and waste tires

By pickling, alkali cracking and hydrogen peroxide activation of waste rubber and waste tires, combined with high-pressure gas crushing technology, nano-grade carbon black with uniform particle size and good dispersion are prepared, which solves the high level of existing carbon black production methods Energy consumption and environmental pollution problems have achieved resource utilization of waste rubber and waste tires and efficient carbon black preparation.

CN119161750APending Publication Date: 2024-12-20JIANGSU LVYUAN RUBBER RESOURCE RECYCLING INNOVATION CENT CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411297235.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing carbon black production methods consume high energy, high raw material costs and environmental pollution. Improper treatment of waste rubber and waste tires lead to environmental pollution, and lack of green carbon black preparation technology to achieve resource utilization.

Method used

By cutting waste rubber and waste tires into rubber fragments, pickling, alkali cracking and hydrogen peroxide activation, the nano-grade carbon black with particle size of 40~80nm is finally prepared by high-pressure gas pulverization technology to achieve the particles of carbon black Uniform diameter and good dispersion.

Benefits of technology

It reduces energy consumption, improves production efficiency, realizes the resource utilization of waste rubber and waste tires, reduces environmental pollution, and the prepared nano-grade carbon black has better functional fillers and black-enhancing agent effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a method for preparing nano-scale carbon black from waste rubber and waste tires, which belongs to the technical field of comprehensive utilization of solid waste resources, and comprises the following steps: (1) crushing waste rubber and / or waste tires into rubber particles with the particle size of not less than 100 meshes; (2) stirring and mixing the rubber particles and an acid solution to form pickled rubber particles; (3) mixing the pickled rubber particles with an alkali solution, removing moisture, and then cracking under the protection of nitrogen to obtain carbon black particles; (4) mixing and activating the carbon black particles and a hydrogen peroxide solution to obtain activated carbon black particles; and (5) carrying out superfine grinding on the activated carbon black particles through high-pressure gas grinding to obtain the nano-scale carbon black. The obtained nano-scale carbon black is uniform in particle size and good in dispersity, and meanwhile resource utilization of waste rubber and / or waste tires is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing nano-level carbon black from waste rubber and waste tires, and belongs to the technical field of comprehensive utilization of solid waste resources. Background Art

[0002] Carbon black is an important functional filler and blackening agent, used in rubber, paint, ink and other industries. Existing industrial carbon black is mainly obtained from hydrocarbon raw materials such as petroleum and natural gas through cracking and combustion, but the raw material cost is high, the production process will produce waste gas causing environmental pollution, and high energy consumption.

[0003] With the rapid development of my country's industry, rubber products, such as tires, have led to an increasing amount of waste rubber, among which the number of waste tires has also gradually increased. If these waste rubber and / or waste tires are not handled properly, they will cause environmental pollution and have a long-term impact on the ecological environment. In order to achieve the comprehensive utilization of waste rubber and / or waste tires and to develop a new carbon black preparation process, it is urgent to seek a green carbon black production method to achieve the resource utilization of waste rubber and / or waste tires. Summary of the invention

[0004] In view of at least one problem existing in the above-mentioned prior art, the present invention provides a method for preparing nano-scale carbon black from waste rubber and waste tires, thereby obtaining nano-scale carbon black with a particle size of 40 to 80 nm. The particle size of the carbon black is uniform and has good dispersibility, while realizing the resource utilization of waste rubber and / or waste tires.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing nano-scale carbon black from waste rubber and waste tires, comprising the following steps: (1) Cut waste rubber and / or waste tires into rubber pieces of 0.5-1 cm in size, and then crush the rubber pieces into rubber particles with a particle size of not less than 100 mesh; (2) mixing the rubber particles with the acid solution, stirring at a low speed for 50 to 60 minutes, and filtering to obtain acid-washed rubber particles; (3) The acid-washed rubber particles are mixed with the alkaline solution, stirred at a low speed and heated to 100-110°C to evaporate the water, then nitrogen is introduced for protection, and the temperature is continued to rise to 500-520°C, and then the temperature is kept for cracking for 20-30 minutes to obtain a solid, which is cooled, acid-washed and neutralized to remove the alkali to neutrality, filtered and washed with water to obtain carbon black particles; (4) mixing the carbon black particles with the hydrogen peroxide solution, adjusting the pH value to ≤4, stirring at a low speed for 30 to 40 minutes at a temperature of 35 to 40°C, filtering and washing with water to obtain activated carbon black particles; (5) The activated carbon black particles are ultrafinely pulverized by high-pressure gas pulverization to obtain nano-grade carbon black.

[0006] Preferably, the rubber particles have a particle size of 100-200 mesh.

[0007] Preferably, in step (4), the carbon black particles are stirred and mixed with the hydrogen peroxide solution, and the pH value is adjusted to a range of 3 to 4.

[0008] Preferably, the nanoscale carbon black particle size is 40-80 nm.

[0009] Preferably, in step (2), the ratio of the amount of the acid solution used is 1 g / 10-15 ml of the rubber particles to the acid solution.

[0010] Preferably, the acid solution is a 5-6.5% (wt) hydrochloric acid solution or a 6-8.5% (wt) sulfuric acid solution; preferably a 5-6.5% (wt) hydrochloric acid solution.

[0011] Preferably, in step (3), the amount of alkaline solution used is: the ratio of rubber particles to alkaline solution is 1 g / 5-8 ml.

[0012] Preferably, the alkaline solution is a 10-15% (wt) sodium hydroxide solution or a 10-15% (wt) potassium hydroxide solution.

[0013] Preferably, the pickling in step (3) is carried out using a 5-6.5% (wt) hydrochloric acid solution or a 6-8.5% (wt) sulfuric acid solution; preferably a 5-6.5% (wt) hydrochloric acid solution.

[0014] Preferably, the ratio of the carbon black particles to the hydrogen peroxide solution is 1 g / 8-12 ml.

[0015] Preferably, the concentration of the hydrogen peroxide solution is 18-20% (wt) hydrogen peroxide solution.

[0016] Preferably, the pH value in step (4) is adjusted by using a 2-3% (wt) hydrochloric acid solution.

[0017] Preferably, the conditions for high-pressure gas pulverization in step (5) are: the gas flow is carbon dioxide, the pulverization pressure is 0.5-0.8 MPa, the injection speed is 400-500 m / s, and the total flow rate is 15-20 m 3 / min.

[0018] Preferably, the rotation speed of the low-speed stirring in step (2) is 300-350 rpm.

[0019] Preferably, the rotation speed of the low-speed stirring in step (3) is 200-250 rpm.

[0020] Preferably, the rotation speed of the low-speed stirring in step (4) is 150-200 rpm.

[0021] The beneficial effects of the present invention are as follows: 1. The present invention first crushes and granulates waste rubber and / or waste tires, increases the contact area and the reaction active surface, and helps to improve production efficiency; 2. The rubber particles of the present invention are first acid-washed and then cracked with the assistance of alkali metal hydroxide, which is beneficial to improving the cracking reaction, generating carbon black particles with finer particle size and darker chroma, while avoiding ash in coarse powder carbon black, and increasing the carbon black yield; 3. After the carbon black particles obtained by cracking of the present invention are activated by hydrogen oxide, the surface micropores and mesopores of the carbon black are increased, which can improve the particle size uniformity and dispersibility of the prepared carbon black; 4. The present invention adopts high-pressure gas pulverization technology, so that the airflow impacts the micropores and mesopores of the activated carbon black particles, which is beneficial to the formation of nano-level carbon black, and the particle size of the nano-level carbon black is uniform and has good dispersibility, while improving production efficiency and reducing energy consumption; 5. The preparation method of the present invention has low energy consumption, easy operation and environmental protection of the process steps, high preparation efficiency, and realizes the resource utilization of waste rubber and / or waste tires, reduces their pollution to the environment, and generates economic and social benefits. DETAILED DESCRIPTION

[0022] The following is a clear and complete description of the technical solutions in the implementation of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents, instruments, and components used, they are all conventional products that can be purchased commercially.

[0023] Example The method for preparing nano-scale carbon black from waste rubber and waste tires comprises the following steps: (1) Cut waste rubber and / or waste tires into rubber pieces of 0.5-1 cm in size, and then crush the rubber pieces into rubber particles with a particle size of not less than 100 mesh; (2) stirring and mixing the rubber particles and the acid solution, stirring and reacting at a rotation speed of 300-350 rpm for 50-60 min, filtering, and obtaining acid-washed rubber particles; wherein the acid solution is a 5-6.5% (wt) hydrochloric acid solution or a 6-8.5% (wt) sulfuric acid solution, and the ratio of the rubber particles to the acid solution is 1 g / 10-15 ml; (3) The acid-washed rubber particles and the alkaline solution are stirred and mixed, stirred at a speed of 200-250 rpm and heated to 100-110°C to evaporate and remove water, then nitrogen is introduced for protection, and the temperature is continued to rise to 500-520°C, and then the temperature is kept for cracking for 20-40 minutes to obtain a solid, which is cooled, acid-washed and neutralized to remove the alkali to neutrality, filtered and washed with water to obtain carbon black particles; wherein the alkaline solution is 10-15% (wt) sodium hydroxide solution or 10-15% (wt) potassium hydroxide solution, and the ratio of rubber particles to alkaline solution is 1g / 5-8ml; (4) stirring and mixing the carbon black particles with 18-20% (wt) hydrogen peroxide solution, adjusting the pH value to 3-4 with 2-3% (wt) hydrochloric acid solution, stirring and reacting at a temperature of 35-40° C. and a rotation speed of 150-200 rpm for 30-40 min, filtering and washing with water to obtain activated carbon black particles; wherein the ratio of carbon black particles to 18-20% (wt) hydrogen peroxide solution is 1 g / 8-12 ml; (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.5~0.8Mpa, the injection speed is 400~500m / s, and the total flow rate is 15~20m 3 / min, forming a powder of 40~80nm and obtaining nano-level carbon black.

[0024] In the present invention, the ratio of rubber particles to acid solution is 1g / 10-15ml, which is conducive to soaking rubber particles. A small volume of acid solution cannot fully soak rubber particles, and a large volume of acid solution prolongs subsequent filtration time. The acid solution is a 5-6.5% (wt) hydrochloric acid solution or a 6-8.5% (wt) sulfuric acid solution. When the concentration of the acid solution is large, the volume of the acid solution used will be reduced, so that the rubber particles are fully contacted with the solution. If the volume of the acid solution is unchanged or increased, the cost of the acid will increase. When the concentration of the acid solution is small, the volume of the acid solution used will be increased, the filtration time will be prolonged, and the production efficiency will be reduced. If the volume of the acid solution is small and unchanged or reduced, the metal impurities in the rubber particles are fully removed. A 5-6.5% (wt) hydrochloric acid solution is preferred.

[0025] In the present invention, the ratio of rubber particles to alkaline solution is 1g / 5-8ml, and there are fine gaps in the acid-washed rubber particles. The volume of the alkaline solution can better ensure effective contact with the acid-washed rubber particles. If the alkaline solution is small, it cannot fully contact with the acid-washed rubber particles. If the volume of the acid solution is large, the subsequent evaporation time is prolonged and the energy consumption is increased. The alkaline solution is a 10-15% (wt) sodium hydroxide solution or a 10-15% (wt) potassium hydroxide solution. When the concentration of the alkaline solution is large, the volume of the alkaline solution used will be reduced, resulting in the acid-washed rubber particles being unable to effectively contact with the alkaline solution. If the volume of the alkaline solution used is reduced, unchanged or increased, the cost of the alkali will be increased. When the concentration of the alkaline solution is small, the volume of the alkaline solution used will be increased, the time for water evaporation will be prolonged, the energy consumption will be increased and the efficiency will be reduced. If the volume of the alkaline solution used is small, unchanged or reduced, the metal impurities in the rubber particles will be fully removed.

[0026] In the present invention, the ratio of carbon black particles to hydrogen peroxide solution is 1g / 8-12ml, which is conducive to soaking the coarse powdered carbon black and making the coarse powdered carbon black fully contact with hydrogen peroxide; the concentration of the hydrogen peroxide solution is 18-20% (wt) of the hydrogen peroxide solution. Under this concentration range, while ensuring that the coarse powdered carbon black is fully contacted with hydrogen peroxide, the coarse powdered carbon black can be fully activated, and the cost of hydrogen peroxide will not be increased.

[0027] Example 1 The method for preparing nano-scale carbon black from waste rubber and waste tires comprises the following steps: (1) Cut waste rubber and waste tires into 0.5-1 cm rubber pieces, and then crush the rubber pieces into 1 kg rubber particles with a particle size of 100-200 mesh; (2) 1 kg of the rubber particles were mixed with 10 L of a 5% (wt) hydrochloric acid solution, stirred at 300 rpm for 50 min, and filtered to obtain acid-washed rubber particles; (3) The acid-washed rubber particles were mixed with 5 L of 10% (wt) sodium hydroxide solution, stirred at 200 rpm and heated to 100-110°C to evaporate the water, then nitrogen was introduced for protection, and the temperature was continued to rise to 500°C, and then the temperature was kept for 20 min to crack to obtain a solid, which was cooled and neutralized with 5% (wt) hydrochloric acid solution to remove the alkali to neutrality, filtered and washed with water to obtain 348 g of carbon black particles (mass after drying, the same below); (4) 345 g of the carbon black particles were mixed with 2.8 L of 20% (wt) hydrogen peroxide solution, and the pH value was adjusted to 3.5 using 2% (wt) hydrochloric acid solution. The mixture was stirred at a temperature of 35-40°C and a rotation speed of 150 rpm for 30 min, filtered and washed with water to obtain activated carbon black particles; (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.5 MPa, the injection speed is 400 m / s, and the total flow rate is 15 m 3 / min, to obtain nano-level carbon black.

[0028] Example 2 The method for preparing nano-scale carbon black from waste rubber and waste tires comprises the following steps: (1) Cut waste rubber and waste tires into rubber pieces of 0.5-1 cm in size, and then crush the rubber pieces into 1 kg of rubber particles with a particle size of 100-200 mesh; (2) 1 kg of the rubber particles were mixed with 12 L of 6.5% (wt) sulfuric acid solution, stirred at 300 rpm for 50 min, and filtered to obtain acid-washed rubber particles; (3) The acid-washed rubber particles were mixed with 7 L of 15% (wt) potassium hydroxide solution, stirred at 200 rpm and heated to 100-110°C to evaporate the water, then nitrogen was introduced for protection, and the temperature was continued to rise to 500°C, and then the temperature was kept for cracking for 20 min to obtain a solid, which was cooled, neutralized with 6.5% (wt) sulfuric acid solution to remove the alkali, filtered and washed with water to obtain 351 g of carbon black particles; (4) 345 g of the carbon black particles were mixed with 2.8 L of 20% (wt) hydrogen peroxide solution, and the pH value was adjusted to 3.2 using 2% (wt) hydrochloric acid solution. The mixture was stirred at a temperature of 35-40°C and a rotation speed of 150 rpm for 30 min, filtered and washed with water to obtain activated carbon black particles. (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.5 MPa, the injection speed is 400 m / s, and the total flow rate is 15 m 3 / min, to obtain nano-level carbon black.

[0029] Example 3 The method for preparing nano-scale carbon black from waste rubber and waste tires comprises the following steps: (1) Cut waste rubber and waste tires into 0.5-1 cm rubber pieces, and then crush the rubber pieces into 1 kg rubber particles with a particle size of 100-200 mesh; (2) 1 kg of the rubber particles were mixed with 15 L of 6.5% (wt) hydrochloric acid solution, stirred at 350 rpm for 60 min, and filtered to obtain acid-washed rubber particles; (3) The acid-washed rubber particles were mixed with 7 L of 12.5% ​​(wt) sodium hydroxide solution, stirred at 250 rpm and heated to 100-110°C to evaporate the water, then nitrogen was introduced for protection, and the temperature was continued to rise to 510°C, and then the temperature was kept for 30 min to crack to obtain a solid, which was cooled and neutralized with 5% (wt) hydrochloric acid solution to remove the alkali to neutrality, filtered and washed with water to obtain 349 g of carbon black particles; (4) 345 g of the carbon black particles were mixed with 2.8 L of 20% (wt) hydrogen peroxide solution, and the pH value was adjusted to 3.4 using 2% (wt) hydrochloric acid solution. The mixture was stirred at a temperature of 35-40° C. and a rotation speed of 200 rpm for 40 min, and then filtered and washed with water to obtain activated carbon black particles. (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.7 MPa, the injection speed is 450 m / s, and the total flow rate is 18 m 3 / min, to obtain nano-level carbon black.

[0030] Example 4 The method for preparing nano-scale carbon black from waste rubber and waste tires comprises the following steps: (1) Cut waste rubber and waste tires into 0.5-1 cm rubber pieces, and then crush the rubber pieces into 1 kg rubber particles with a particle size of 100-200 mesh; (2) 1 kg of the rubber particles were mixed with 12 L of 6% (wt) hydrochloric acid solution, stirred at 350 rpm for 60 min, and filtered to obtain acid-washed rubber particles; (3) The acid-washed rubber particles were mixed with 8 L of 15% (wt) sodium hydroxide solution, stirred at 250 rpm and heated to 100-110°C to evaporate the water, then nitrogen was introduced for protection, and the temperature was continued to rise to 520°C, and then the temperature was kept for 25 min to crack to obtain a solid, which was cooled and neutralized with 5% (wt) hydrochloric acid solution to remove the alkali to neutrality, filtered and washed with water to obtain 348 g of carbon black particles; (4) 345 g of the carbon black particles were mixed with 2.8 L of 20% (wt) hydrogen peroxide solution, and the pH value was adjusted to 3.7 using 2% (wt) hydrochloric acid solution. The mixture was stirred at a temperature of 35-40° C. and a rotation speed of 200 rpm for 40 min, and then filtered and washed with water to obtain activated carbon black particles. (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.8 MPa, the injection speed is 500 m / s, and the total flow rate is 20 m 3 / min, to obtain nano-level carbon black.

[0031] Example 5 The method for preparing nano-scale carbon black from waste rubber and waste tires comprises the following steps: (1) Cut the waste rubber into 0.5-1 cm rubber pieces, and then crush the rubber pieces into 1 kg rubber particles with a particle size of 100-200 mesh; (2) 1 kg of the rubber particles were mixed with 12 L of a 5% (wt) hydrochloric acid solution, stirred at 350 rpm for 60 min, and filtered to obtain acid-washed rubber particles; (3) The acid-washed rubber particles were mixed with 7 L of 15% (wt) sodium hydroxide solution, stirred at 250 rpm and heated to 100-110°C to evaporate the water, then nitrogen was introduced for protection, and the temperature was continued to rise to 520°C, and then the temperature was kept for 25 min to crack to obtain a solid, which was cooled and neutralized with 5% (wt) hydrochloric acid solution to remove the alkali to neutrality, filtered and washed with water to obtain 348 g of carbon black particles; (4) 340 g of the carbon black particles were mixed with 4 L of 20% (wt) hydrogen peroxide solution, and the pH value was adjusted to 3.4 using 2% (wt) hydrochloric acid solution. The mixture was stirred at a temperature of 35-40° C. and a rotation speed of 200 rpm for 40 min, and then filtered and washed with water to obtain activated carbon black particles. (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.8 MPa, the injection speed is 450 m / s, and the total flow rate is 10 m 3 / min, to obtain nano-level carbon black.

[0032] Example 6 The method for preparing nano-scale carbon black from waste rubber and waste tires comprises the following steps: (1) Cut the waste tires into 0.5-1 cm rubber pieces, and then crush the rubber pieces into 1 kg of rubber particles with a particle size of 100-200 mesh; (2) 1 kg of the rubber particles were mixed with 15 L of 6.5% (wt) hydrochloric acid solution, stirred at 350 rpm for 60 min, and filtered to obtain acid-washed rubber particles; (3) The acid-washed rubber particles were mixed with 6 L of 10% (wt) sodium hydroxide solution, stirred at 250 rpm and heated to 100-110°C to evaporate the water, then nitrogen was introduced for protection, and the temperature was continued to rise to 510°C, and then the temperature was kept for 25 min to crack to obtain a solid, which was cooled and neutralized with 5% (wt) hydrochloric acid solution to remove the alkali to neutrality, filtered and washed with water to obtain 347 g of carbon black particles; (4) 340 g of the carbon black particles were mixed with 3.5 L of 18% (wt) hydrogen peroxide solution, and the pH value was adjusted to 3.8 using 2% (wt) hydrochloric acid solution. The mixture was stirred at a temperature of 35-40° C. and a rotation speed of 200 rpm for 40 min, filtered and washed with water to obtain activated carbon black particles. (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.8 MPa, the injection speed is 400 m / s, and the total flow rate is 12 m 3 / min, to obtain nano-level carbon black.

[0033] Comparative Example 1 The difference from Example 1 is that: the rubber particles in step (1) have a particle size of 40-60 mesh; 353 g of carbon black particles are obtained in step (3); and under the same high-pressure gas pulverization conditions and ultrafine pulverization time as in the example, carbon black is formed in step (5) of comparative example 1.

[0034] In addition, it was found that when the rubber particles have a particle size greater than 200 mesh, the particle size of the carbon black particles obtained after treatment and the ash content they contain are slightly different from the particle size of the carbon black particles after treatment of the rubber particles of the present invention and the ash content they contain, and nano-level carbon black less than 80nm can be obtained, and the particle size dispersion is good; however, when the rubber particles have a particle size greater than 200 mesh, crushing requires more time and energy.

[0035] Comparative Example 2 The difference from Example 1 is that in step (4), 345 g of carbon black particles are stirred and mixed with 2.8 L of 20% (wt) hydrogen peroxide solution, and the pH value is adjusted to 4.5 using 2% (wt) hydrochloric acid solution; under the same high-pressure gas pulverization conditions and ultrafine pulverization time of the embodiment, carbon black is formed in step (5) of comparative example 2.

[0036] In addition, it was found that when the carbon black particles were activated at a pH less than 3, under the same high-pressure gas pulverization conditions and ultrafine pulverization time as in Example 1, nano-scale carbon black less than 80 nm could be obtained, and the particle size dispersion was good; however, the smaller the pH obtained, the more acid was consumed, and the more water was consumed in the subsequent washing.

[0037] Comparative Example 3 The difference from Example 1 is that in step (5), the activated carbon black particles are ground in a sand mill to form carbon black.

[0038] Comparative Example 4 The difference from Example 1 is that in step (3), the carbon black particles are not activated by hydrogen peroxide, and in step (4), the carbon black particles are ultrafinely pulverized by high-pressure gas pulverization, the gas flow is carbon dioxide, the pulverizing gas pressure is 0.5 MPa, the injection speed is 400 m / s, and the total flow rate is 15 m 3 / min, and the ultrafine grinding time is the same as that in Example 1 to form carbon black.

[0039] Comparative Example 5 The difference from Example 1 is that: in step (2), 1 kg of rubber particles are mixed with 5 L of 10% (wt) sodium hydroxide solution, stirred at a speed of 200 rpm and heated to 100-110°C to evaporate and remove water, then nitrogen is introduced for protection, and the temperature is continued to be raised to 500°C, and then the temperature is kept for cracking for 30 minutes, cooled to obtain a solid, cooled, and neutralized with 5% (wt) hydrochloric acid solution to remove the alkali to neutrality, filtered and washed with water to obtain 423 g of carbon black particles (mass after drying); the rubber particles are first cracked with the assistance of sodium hydroxide, and it is found that the rubber particles are not completely cracked.

[0040] Comparative Example 6 The difference from Example 1 is that: (2) 1 kg of rubber particles were mixed with 5 L of 10% (wt) sodium hydroxide solution, stirred at 200 rpm and heated to 100-110°C to evaporate water, then nitrogen was introduced for protection, and the temperature was continued to rise to 500°C, and then the temperature was kept for cracking for 55 min, cooled to obtain a solid, cooled, and neutralized with 5% (wt) hydrochloric acid solution to remove the alkali to neutrality, filtered and washed with water to obtain 354 g of carbon black particles (mass after drying); (3) mixing the carbon black particles with 10 L of a 5% (wt) hydrochloric acid solution at 300 rpm for 50 min, and filtering to obtain acid-washed carbon black particles; (4) 330 g of the above-mentioned acid-washed carbon black particles were mixed with 2.8 L of 20% (wt) hydrogen peroxide solution, and the pH value was adjusted to 3.6 using 2% (wt) hydrochloric acid solution. The mixture was stirred at a temperature of 35-40°C and a rotation speed of 150 rpm for 30 min, filtered and washed with water to obtain activated carbon black particles; (5) The activated carbon black particles are crushed by high-pressure gas for ultrafine grinding. The gas flow is carbon dioxide, the crushing pressure is 0.5 MPa, the injection speed is 400 m / s, and the total flow rate is 15 m 3 / min, and the ultrafine grinding time is the same as that in Example 1 to form carbon black.

[0041] The carbon black particles and product carbon black of Examples 1 to 6 and Comparative Examples 1 to 6 were analyzed, and the results are shown in Table 1.

[0042] Table 1

[0043] In summary, the method for preparing nano-scale carbon black from waste rubber and waste tires of the present invention obtains nano-scale carbon black with a particle size of 40-80 nm, the particle size of the carbon black is uniform, and the dispersibility is good, and the resource utilization of waste rubber and / or waste tires is achieved at the same time; the preparation method of the present invention has low energy consumption, the process steps are easy to operate and environmentally friendly, and the preparation efficiency is high; the nano-scale carbon black of the present invention has a better effect as a functional filler and a blackening agent.

[0044] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0045] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. Method for preparing nano-scale carbon black from waste rubber and waste tires. It is characterized in that The following steps are involved: (1) Cut waste rubber and / or waste tires into rubber pieces of 0.5-1 cm in size, and then crush the rubber pieces into rubber particles with a particle size of not less than 100 mesh; (2) stirring and mixing the rubber particles and the acid solution, stirring and reacting at a speed of 300-350 rpm for 50-60 min, and filtering to obtain acid-washed rubber particles; (3) stirring and mixing the acid-washed rubber particles and the alkaline solution, stirring at a speed of 200-250 rpm and heating to 100-110° C. to evaporate and remove water, then introducing nitrogen protection, continuing to heat to 500-520° C., then keeping the temperature for cracking for 20-30 minutes to obtain a solid, cooling, acid-washing and neutralizing to remove the alkali to neutral, filtering and washing with water to obtain carbon black particles; (4) stirring and mixing the carbon black particles and the hydrogen peroxide solution, adjusting the pH value to ≤4, stirring and reacting at a temperature of 35-40°C and a rotation speed of 150-200 rpm for 30-40 minutes, filtering and washing with water to obtain activated carbon black particles; (5) The activated carbon black particles are ultrafinely pulverized by high-pressure gas pulverization to obtain nano-scale carbon black with a particle size of 40 to 80 nm.

2. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 1, It is characterized in that In step (1), the particle size of the rubber particles is 100-200 mesh.

3. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 1, It is characterized in that In step (4), the carbon black particles are stirred and mixed with the hydrogen peroxide solution, and the pH value is adjusted to a range of 3 to 4.

4. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 1, It is characterized in that The amount of acid solution used in step (2): the ratio of rubber particles to acid solution is 1g / 10~15ml.

5. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 4, It is characterized in that The acid solution is a 5-6.5% (wt) hydrochloric acid solution or a 6-8.5% (wt) sulfuric acid solution.

6. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 1, It is characterized in that The amount of alkaline solution used in step (3) is: the ratio of rubber particles to alkaline solution is 1g / 5~8ml.

7. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 6, It is characterized in that The alkaline solution is a 10-15% (wt) sodium hydroxide solution or a 10-15% (wt) potassium hydroxide solution.

8. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 1, It is characterized in that The ratio of the carbon black particles to the hydrogen peroxide solution is 1 g / 8-12 ml.

9. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 8, It is characterized in that The concentration of the hydrogen peroxide solution is 18-20% (wt) hydrogen peroxide solution.

10. The method for preparing nano-scale carbon black from waste rubber and waste tires according to claim 1, It is characterized in that The conditions for high pressure gas pulverization in step (5) are: the gas flow is carbon dioxide, the pulverization pressure is 0.5-0.8 MPa, the injection speed is 400-500 m / s, and the total flow rate is 15-20 m 3 / min.

Citation Information

Cited By

  • Modified lignin / regenerated carbon black premix, tread rubber composition and preparation methods of modified lignin / regenerated carbon black premix and tread rubber composition

    CN121991521A

  • A modified lignin / regenerated carbon black premix, a tread rubber composition, and a method for preparing the same

    CN121991521B